MONITORING DALAM MANAJEMEN SARANA DAN PR - S. Nor Hasanah (IAIN Ambon, 2018)
Abstract: Monitoring in school and security asset of education system of facilities and infra structures management based on vision and mission, therefore education institution needs to develop a management system includes planning, procurement, utilization, maintenance, deletion and updating all facilities and infrastructures. Education Institution must have special guidance about completeness and adequacy the needs of facilites and infrastructures, includes inventary classification system and information of existence. Besides that, education institution must have management system that guarantee wider access existence especially for the students and teacher through sharing resource model applied. Paradigm monitoring and evaluating toward facility and infrastructures of an education instution. so that can be described some essences of sub discussion emerging high quality and effective education, and efficient through facilities and infrastuctures management, evaluating in education of facilities and infrastructures and critical analiysis toward monitoring and evaluating of facilities and Infrastructures. Key words : monitoring, facilities and infrastuctures of education.